Composition of the genus Connexochiton Kaas, 1979 (Mollusca: Polyplacophora: Ischnochitonidae) - Sirenko, Boris (Zootaxa, 2021)
The species composition of the genus Connexochiton is revised. So far, six Recent species of the genus Connexochiton have been known: C. platynomenus, C. kaasi, C. crassus, C. bromleyi, C. moreirai and C. discernibilis After the present revision, the genus consists of Connexochiton platynomenus, C. kaasi, C. crassus, as well as three new species, C. costatus n. sp. from the Philippines, C. kermadeci n. sp. from New Zealand and C. solomonicus n. sp. from the Solomon Islands. Connexochiton discernibilis was assigned to the ischnochitonid genus Stenosemus (now Stenosemus discernibilis). Connexochiton bromleyi and C. moreirai are transferred back to the genus Ischnochiton. Principle features of the genus Connexochiton include: a distinctive shape of the valves with the hind edge of the intermediate valves noticeably turned down, which makes the lateral areas narrow and appearing strongly raised; tegmentum delicately sculptured by quincuncially arranged triangular granules that form an alveolate pattern; each granule has 9 to 11 aesthete pores; apophyses are connected medially by a short jugal plate, dorsal scales of the girdle are strongly bent, with short longitudinal ribs or spherules or both; head of the major lateral teeth of radula is unicuspid and sickle-shaped. An identification key for the species of the genus Connexochiton is provided.